Peningkatan Motivasi Dan Hasil Belajar Materi Luas Bangun Datar Melalui Model Pembelajaran STAD Pada Siswa Kelas V SD 2 Besito - Sudiyarto Sudiyarto (Journal Prakarsa Paedagogia, 2018)
Based on the results of the observation, it was shown that the motivation and learning outcomes of material in the broad wake of students of class V SD 2 Besito were still low. The motivation for average learning is 72.92% and students who complete their learning outcomes are only 50%. For this reason, researchers using the STAD learning model to improve both. Because the STAD learning model has the advantage that higher mental functions will appear in conversations or cooperation between individuals. From the research conducted for two cycles, conclusions were obtained, namely through the application of the STAD learning model to increase learning motivation to 91.66%, and learning completeness to 91%.